Synthesis of trans‐A2B2‐ and trans‐A2BC‐Porphyrins with Polar 4′‐(Dimethylamino)tolan‐4‐yl Substituents, and a Screening Protocol for Vapor‐Phase Deposition on Metal Surfaces. Issue 26 (30th July 2014) - Alberti, Mariza N.; Nowakowska, Sylwia; Tzirakis, Manolis D.; Nowakowski, Jan; Fesser, Petra; Schweizer, W. Bernd; Shchyrba, Aneliia; Thilgen, Carlo; Jung, Thomas A.; Diederich, François
Abstract: The role of polar 4‐[ p ‐(dimethylamino)phenylethynyl]phenyl substituents, with a calculated dipole moment of 3.35 Debye, in the self‐assembly of trans ‐A2 B2 ‐ and A2 BC‐substituted porphyrins was explored in the solid state by X‐ray crystallography, and on an Au(111) surface by scanning tunneling microscopy (STM). Our results demonstrate that the dipolar character of these substituents blocks the 2D self‐assembly of porphyrins into larger ordered domains on Au(111) at low coverage, whereas antiparallel dipole–dipole interactions govern the molecular ordering in the crystal. The STM analysis revealed an adaptation of the conformation of the prochiral building blocks and a site‐selectivity of the adsorption. We present a general protocol for testing the suitability of higher‐molecular‐weight compounds, such as porphyrins, to be deposited on surface by sublimation in ultra‐high vacuum (UHV). This protocol combines classical methods of chemical analysis with typical surface science techniques. Abstract : In the context of exploring the role of the polar 4′‐(dimethylamino)tolan‐4‐yl group in 3D (single crystals) and 2D [on Au(111)] self‐assembly of tetraarylporphyrins, we synthesized and fully characterized a series of meso ‐substituted trans ‐porphyrins. A reliable protocol was developed to test the suitability of molecules for intact deposition on surfaces by sublimation in ultra‐high vacuum.